VIBRATION ANALYSIS OF AN EVAPORATOR USING CHEMCAD - SAMEER M. WAGH,; DIVYA P. BARAI,; MEGHA H. TALWEKAR, (International Journal of Innovations in Engineering Research and Technology, 2021)
CHEMCAD is a powerful and effective software tool for chemical process simulation. Evaporator consists of a heat exchanger for boiling the solution with special provisions for separation of liquid and vapourphases.Calandria Evaporator also called as short-tube vertical evaporators are widely usedin industries.In this paper, the vibration analysis for acalandria evaporator is carried out using CHEMCAD. The change in the values of cross flow velocity, critical velocity, vortex shedding frequency,turbulent buffeting frequencyand natural frequencythroughout the length of tube is noted and graphs are plotted for every vibration mechanism against the tube length. It is observed that these vibration mechanisms increase from inlet to the center but decrease as they approach to the outlet.This kind of analysis is reported to be one of the basic ways tostudy the vibration mechanisms incalandria evaporator.